A STUDY ON THE AVIAN (PASSERINE) DIVERSITY OF LAHORE - S. Fazal; Z. Ali; F. Manzoor; A. Nazir (Journal of Animal and Plant Sciences, 2014)
A study was carried out to find the local status and population count of selected passerine birds species in Lahore during 2008. Comparison was made by relating the population density of passerine birds with reference to flora of 3 old and 3 new sites in and around Lahore. The results of the study revealed that the changing habitat of Lahore due to human disturbance and non-availability of breeding sites for birds was the main reason behind the loss of passerine avian diversity. Secondly, the trend of planting decorative or ornamental plants such as Eucalyptus in Lahore was the key factor forcing birds to migrate. Relative abundance of native trees and density of observed passerine bird species was higher in old reference sites rather than in newly established parks of Lahore city because new parks in the city have highly disturbed habitat and more exotic tree varieties. Results of the present study revealed that one of the new parks,  woodland wildlife park outside the city is still providing the natural habitat to birds due to less human disturbance. So there is dire need to build such parks which have more natural environment. Conservation of passerine avian diversity within city area can be progressed by managing the urban green space and plantation of native flora. After completion of study, it was recommended that only ecological restoration of damaged habitat at Lahore can turn back the tide of biodiversity loss.
Keywords: Avian fauna; biodiversity; passerine; habitat